PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MELALUI METODE PEMBELAJARAN THINKING ALOUD PAIR PROBLEM SOLVING (TAPPS) - Rike Arami Rezeki; M. Duskri; Muhammad Yani (Mathieu : Journal of Mathematics Education and Learning, 2025)
Problem-solving ability is a crucial mathematical skill; however, students’ performance in this area remains relatively low. To address this issue, the Thinking Aloud Pair Problem Solving (TAPPS) method is assumed to enhance students’ mathematical problem-solving abilities. This study aims to (1) examine the improvement of students’ problem-solving skills after the implementation of TAPPS in Grade VII SMP, and (2) compare the improvement between students taught with TAPPS and those taught using conventional methods. The research employed a quasi-experimental design with a pretest-posttest control group. The population consisted of Grade VII students of SMP Negeri 16 Takengon, with class VII1 chosen as the experimental group and VII2 as the control group through random sampling. Data were collected through tests and analyzed using the t-test. Findings showed that the experimental group achieved an average N-gain of 0.40 (moderate effectiveness). Moreover, tcount = 7.67 > ttable = 1.68, indicating that TAPPS was significantly more effective than conventional teaching in improving students’ mathematical problem-solving skills.